Mobilizing Shakti: Hindu Goddesses and Campaigns Against Gender-Based Violence - Smears, Ali (Religions, 2019)
Hindu goddesses have been mobilized as powerful symbols by various groups of activists in both visual and verbal campaigns in India. Although these mobilizations have different motivations and goals, they have frequently emphasized the theological association between goddesses and women, connected through their common possession of Shakti (power). These campaigns commonly highlight the idea that both goddesses and Hindu women share in this power in order to inspire women to action in particular ways. While this association has largely been used as a campaign strategy by Hindu right-wing women's organizations in India, it has also become a strategy employed in particular feminist campaigns as well. This article offers a discourse analysis of two online activist campaigns (Priya's Shakti and Abused Goddesses) which mobilize Hindu goddesses (and their power) in order to raise awareness about gender-based violence in India. I examine whether marginalized identities of women in India, in relation to caste, class and religious identity, are represented in the texts and images. To do so, I analyze how politically-charged, normative imaginings of Indian women are constructed (or maintained). This analysis raises questions about the usefulness of employing Hindu goddesses as feminist symbols, particularly in contemporary Indian society, in which communal and caste-based tensions are elevated.